Closed reduction and minimally invasive surgical treatment of type IIIa fragility fractures of the pelvis associated with ipsilateral periprosthetic femur fracture: A case report. (December 2020) - Yanagisawa, Yohei; Watanabe, Yu; Matsumoto, Yukei; Makihara, Takeshi; Inoue, Yoshiaki; Yamazaki, Masashi
Abstract: Patients with fragility fractures of the pelvic ring (FFP) are elderly and, from the perspective of surgical invasion, percutaneous and stable fixation may be a superior surgical method than open reduction and internal fixation (ORIF). While in the case of FFP type IIIa, ORIF, as a rule, typically requires open reduction of the displaced ilium via an anterior intrapelvic approach and/or lateral window of the ilioinguinal approach. We have reported here the case of an 89-year-old woman who suffered from FFP type IIIa with ipsilateral periprosthetic femur fracture that was surgically treated. The iliac fracture was approached in a minimally invasive manner using the traction operation while preparing for femoral shaft fracture surgery, which did not require open reduction, and showed favorable outcomes.